Autistic Identity Development and Postsecondary Education - Gobbo, Ken; Shmulsky, Solvegi (Disability Studies Quarterly, 2016)
As the diagnosis of autism spectrum disorder (ASD) becomes more prevalent in society and an autistic culture develops and moves forward, colleges and universities are in the position of supporting students with similar differences but opposing views about how to address those differences. The autism acceptance movement emphasizes the need for change by educational institutions and society at large, while the medical model perspective seeks to understand cause and believes autistic people need treatment and even need to be cured of autism. This article uses a disability identity development model to explore the potential impact of autism acceptance and medical model perspectives at different stages of development. Postsecondary program elements that emphasize neurodiversity, understanding strengths, and the building of academic strategies for success that support students who are in the process of identity development are recommended.